UJI KETEBALAN DAN KEKERASAN LAPISAN CHROM KERAS PLAT BAJA ST 37 - Akhmad Syarief (INFO-TEKNIK, 2007)
Crhome plated processing has excellency rather than to others type of plating. Its excellence is : the resistance from worn out, crhome plated resists to gas interference and the temperature under 500 0C.Reseach methodology which is being done is experiment, in which is being tested as the sample of steel ST 37 product that is being plated with hard chrome. The testing is being done, invelop the test of hardness and thickness of chrome on steel ST 37.Hard chrome plated increases the thickness and hardness also reduce the friction coefficient and change the performance /surface of the object being plated, the hardness of hard chrome plated is also interferred by use of tight current and interferred by the processing time, at the liquid concentration 200 gr/lt Cr03 and 2,0 gr/lt H2SO4, and the thickness of hard chrome plated is interferred by tight current and also is interferred by the processing time, in the liquid concentration 200 gr/lt Cr03 and 2,0 gr/lt H2SO4.